Eksplorasi Kinerja Keuangan Desa Wisata Berdasarkan Rasio Profitabilitas Dan Pengaruh Dari Inovasi Produk - Umi Nurjanah; Fathor AS (Universitas Veteran Bangun Nusantara, 2023)
The purpose of this study is to determine the financial performance of tourism villages based on profitability ratios, to analyze the relationship between the company's financial performance and the level of product innovation. The sample in this study is financial statements in a certain period using purpossive sampling techniques. This research approach is quantitative with simple profitability ratio and linear regression analysis techniques. Based on the results of the study, during 2022-2023 the profitability of the Kedatim Mangrove Tourism Destination has decreased significantly, and the results of a simple linear regression analysis found no significant effect of product innovation on financial performance.